2024
DOI: 10.1001/jamapsychiatry.2023.5068
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Optimism and Objective Measures of Physical Functioning in Women

Hayami K. Koga,
Francine Grodstein,
David R. Williams
et al.

Abstract: ImportanceIdentifying factors contributing to sustained physical functioning is critical for the health and well-being of the aging population, especially as physical functioning may precede and predict subsequent health outcomes. Prior work suggests optimism may protect health, but less is known about the association between optimism and objective physical functioning measures as individuals age.ObjectiveTo evaluate the longitudinal association between optimism and 3 physical functioning measures.Design, Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In Reply We thank Cheung et al for their thoughtful letter and the opportunity to discuss some of the limitations of our study . Cheung and colleagues suggest that determining optimism based on initial levels of optimism may be biased as levels of optimism may change over time.…”
mentioning
confidence: 92%
“…In Reply We thank Cheung et al for their thoughtful letter and the opportunity to discuss some of the limitations of our study . Cheung and colleagues suggest that determining optimism based on initial levels of optimism may be biased as levels of optimism may change over time.…”
mentioning
confidence: 92%
“…To the Editor It was with great interest and appreciation that we read the article by Koga et al, which found that, in postmenopausal women, higher optimism at baseline was associated with better performance on measures of physical functioning over time, including less decline in walking speed and number of chair stands over a 6-year follow-up. However, the limitations of this study should be considered when interpreting its conclusions.…”
mentioning
confidence: 99%